2017
DOI: 10.1002/2017ja024143
|View full text |Cite
|
Sign up to set email alerts
|

Modeling radiation belt dynamics using a 3‐D layer method code

Abstract: A new 3‐D diffusion code using a recently published layer method has been developed to analyze radiation belt electron dynamics. The code guarantees the positivity of the solution even when mixed diffusion terms are included. Unlike most of the previous codes, our 3‐D code is developed directly in equatorial pitch angle (α0), momentum (p), and L shell coordinates; this eliminates the need to transform back and forth between (α0,p) coordinates and adiabatic invariant coordinates. Using (α0,p,L) is also convenie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 90 publications
(137 reference statements)
0
16
0
Order By: Relevance
“…Xiao et al (2014) calculated drift and bounce-averaged diffusion coefficients based on observed chorus spectra and used them in numerical simulations to demonstrate that the observed lower-band chorus waves could cause the observed increase in electron fluxes within 15 hr. Wang et al (2017) concluded that the rapid enhancement of radiation belt flux resulted from the combination of transport by radial diffusion of a seed electron population and subsequent local acceleration driven by chorus waves, and Ma et al (2018), who incorporated both local electron heating by chorus waves and radial transport in their simulation, concluded that resonant interaction with chorus waves was the dominant process that accounted for the electron flux enhancement, particularly near the location of the flux peak. Figure 16a shows a sudden jump in solar wind pressure associated with an interplanetary shock near 06:00 UT on 17 March from~1 nPa to over 7 nPa.…”
Section: Stormtime Enhancement: 17-19 March 2013mentioning
confidence: 99%
“…Xiao et al (2014) calculated drift and bounce-averaged diffusion coefficients based on observed chorus spectra and used them in numerical simulations to demonstrate that the observed lower-band chorus waves could cause the observed increase in electron fluxes within 15 hr. Wang et al (2017) concluded that the rapid enhancement of radiation belt flux resulted from the combination of transport by radial diffusion of a seed electron population and subsequent local acceleration driven by chorus waves, and Ma et al (2018), who incorporated both local electron heating by chorus waves and radial transport in their simulation, concluded that resonant interaction with chorus waves was the dominant process that accounted for the electron flux enhancement, particularly near the location of the flux peak. Figure 16a shows a sudden jump in solar wind pressure associated with an interplanetary shock near 06:00 UT on 17 March from~1 nPa to over 7 nPa.…”
Section: Stormtime Enhancement: 17-19 March 2013mentioning
confidence: 99%
“…The selected events were “St. Patrick's Day” storm time enhancement: 17 March 2013 through 19 March 2013 (e.g., Boyd et al, ; Hudson et al, ; Z. Li et al, ; W. Li et al, ; Ma et al, ; Olifer et al, ; Shprits et al, ; Ukhorskiy et al, ; Wang et al, ; Xiao et al, ). “Children's Day” storm time dropout: 31 May 2013 through 3 June 2013 (e.g., Clilverd et al, ; Kang et al, ). “International Talk Like a Pirate Day” nonstorm enhancement: 19 September 2013 through 21 September 2013 (e.g., Ma et al, ; Pakhotin et al, ). “National Punctuation Day” nonstorm dropout: 23 September 2013 through 26 September 2013 (e.g., Capannolo et al, ; Pakhotin et al, ; Su et al, ). A key part of the challenge activity was the collection—in publicly accessible cloud storage—of supporting data, especially of the type used for setting model boundary conditions or incorporating physical processes. As the community continues to move toward open data practices this type of activity will become less necessary, but it proved to be a great community resource for modelers engaging in the FG.…”
Section: Rb Dropout and Rb Buildup Challengesmentioning
confidence: 99%
“…Present 3‐D radiation belt models generally either set the minimum energy to a constant value throughout the calculation region (e.g., Tu et al, ; Wang et al, ) or the minimum energy is defined by a line of constant first adiabatic invariant, μ (e.g., Albert et al, ; Glauert et al, ). Here we formulate the 90° electron flux at energies following a line of first adiabatic invariant to explore using the presented methods to generate low‐energy boundaries for models like the British Antarctic Survey (BAS) Radiation Belt Model (Glauert et al, ).…”
Section: Using the Poes Data To Form A Low‐energy Boundary Conditionmentioning
confidence: 99%